Service Quality of Organizations Providing Long- Term Social Care - Geciene, Jolita; Raisiene, Agota Giedre (European Scientific Journal, ESJ, 2018)
The article presents an evaluation of social care quality following the EQUASS methodology. The evaluation was carried out considering the aspects of institutional care reform and factors of intersectoral collaboration and partnership between organizations providing social services which are important for the spread of good practice, more effective institution management and optimization of state resource use. In addition, the article discusses the requirements for social care institutions‘ service quality, analyzes the main models for service quality assessment applied in Lithuania and the EU. The research has shown that based on the evaluation of research subjects, the social care institutions‘ service quality is quite high. The quality of services could be improved by eliminating the weaknesses of intersectoral collaboration.